2016
DOI: 10.1063/1.4960465
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance characteristics and tunable sensor performances of plasmonic graphene ribbons

Abstract: We investigate the transmittance characteristics of graphene ribbons numerically. It is found that the transmission dips originate from the transverse and longitudinal resonances of edge graphene plasmon modes, supported by the graphene ribbon resonator. The environmental refractive index changes are detected by measuring the resulting spectral shifts of the resonant transmission dip, so the graphene ribbons can be applied to plasmonic sensor in infrared. Simulation results show that sensing performances for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A comparison with the literature indicates that other graphene-based refractive index sensors [54][55][56], have been designed in the mid infrared wavelengths with the maximum sensitivity values of 1040, 590, and 1445 nm/RIU, respectively. In [57], a refractive index sensor based on the graphene ribbons is proposed with the sensitivity in the range of 2700-3100 nm/RIU. Also, in [58], a sensitivity up to 4525 nm/RIU has been achieved.…”
Section: Refractive Index Sensormentioning
confidence: 99%
“…A comparison with the literature indicates that other graphene-based refractive index sensors [54][55][56], have been designed in the mid infrared wavelengths with the maximum sensitivity values of 1040, 590, and 1445 nm/RIU, respectively. In [57], a refractive index sensor based on the graphene ribbons is proposed with the sensitivity in the range of 2700-3100 nm/RIU. Also, in [58], a sensitivity up to 4525 nm/RIU has been achieved.…”
Section: Refractive Index Sensormentioning
confidence: 99%
“…It is found that graphene plasmonic EPs increases from 31.89 to 39.38 THz, as shown in figure 6(h). The EPs blueshift with increasing E f , the reason being that the decrease of Re(n eff ) with E f leads to the blueshift of the resonant frequencies for resonators A and B [40,41]. The forward reflection of the system is always near to 0, the backward reflection is >26%, and the reflection contrast ratios are also always >0.99 at graphene plasmonic EPs.…”
Section: Resultsmentioning
confidence: 95%
“…The fundamental edge graphene surface plasmon polaritons mode (EGSPPs) propagates along the ribbon waveguide [40,41], and we can use TCMT to analyze the dynamical propagation of EGSPPs. The time evolutions of EGSPPs' amplitudes a and b can be obtained by the following equations:…”
Section: Structure and Tcmtmentioning
confidence: 99%
“…4 plots the magnetic field distributions |H z | for λ = 29.24µm(a), 21.04µm(b), 17.12µm(c), 16.66µm(d), 14.42µm(e), 13.06µm(f), 12.38µm(g), 11.54µm(h), and 11µm(i), respectively. The anti-symmetrical distribution |H z | in the ring structure demonstrate the fundamental EGPs modes are excited, which are the same with Fig.…”
Section: Transmittance Characteristicsmentioning
confidence: 99%